2022
DOI: 10.1111/ddi.13593
|View full text |Cite
|
Sign up to set email alerts
|

Elevational patterns of amphibian functional and phylogenetic structures in eastern Nepal Himalaya

Abstract: Aim Exploring the mechanism underlying community assembly processes is considered as one of the central topics for biogeography. As one of the biodiversity hotspots, Nepal Himalaya has attracted increasing attention during the past decade. However, the main processes shaping amphibian assemblages in this area are still unclear. Here, we examined the elevational patterns of amphibian functional and phylogenetic structures to understand the main mechanism driving amphibian assemblages along an elevational gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 104 publications
2
11
0
Order By: Relevance
“…The variations of phylogenetic diversity with elevations were variable across different taxa in different mountains [ 60 ]. In our studied nature reserve, the PD values of amphibians also showed a hump-shaped relationship with elevation, which was similar to other reported mountainous areas, such as the eastern Himalayas of Nepal [ 20 ]. Interestingly, the elevations of 300–500 m seemed to have the maximum PD value, which could be explained by the presence of evolutionary key species which are narrowly distributed along low elevations [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The variations of phylogenetic diversity with elevations were variable across different taxa in different mountains [ 60 ]. In our studied nature reserve, the PD values of amphibians also showed a hump-shaped relationship with elevation, which was similar to other reported mountainous areas, such as the eastern Himalayas of Nepal [ 20 ]. Interestingly, the elevations of 300–500 m seemed to have the maximum PD value, which could be explained by the presence of evolutionary key species which are narrowly distributed along low elevations [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…To create effective conservation schemes and management strategies, it is important to know the various community structures that underpin and support the present biodiversity in the ecosystem [ 2 ]. Most studies focus only on the taxonomic element of species, regarding species as ecologically identical entities when analyzing how communities are formed [ 20 ]. Taxonomic diversity indices (e.g., species richness, Simpson index, and Shannon–Weiner index) reflect certain characteristics of species diversity to some extent, such as the abundance of species and the uniformity of their distribution [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community structure and its assembly mechanisms are not constant across mountain ecosystems (Du et al, 2021; Wang et al, 2022; Zhao et al, 2022). We tested the variations in standardized β‐diversity among communities to assess the potential assembly processes.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian communities exhibit diverse patterns in response to environmental and geographical gradients (Dalmolin et al, 2019; Leao‐Pires et al, 2018; Zhao et al, 2022). Elevational distance when considered a proxy of the dispersal limitation (Basham et al, 2019), greatly influenced species replacement and loss/gain among communities.…”
Section: Discussionmentioning
confidence: 99%
“…Still in Asia, Zhao et al (2022) showed that both elevation and environmental variations (e.g. air temperature, the number of tree stumps, the number of trees showing looping, the number of trees and water pH) drive the spatial distribution of amphibian functional and phylogenetic diversity patterns in eastern Nepal Himalaya.…”
Section: This Issuementioning
confidence: 99%